Restoration of antibiotic associated diarrhea induced gut microbiota disorder by using Dictyophora indusiata water-insoluble polysaccharides in C57BL/6J mice - Lai, Yong; Zhang, Qifan; Xu, Maohan; Guo, Xiurong; Zhou, Quan; Liu, Qiuyu; Deng, Huiling; Song, Can (Frontiers in Nutrition, 2025)
BackgroundA healthy gut depends on a balance of commensal and probiotic bacteria, and prolonged and inappropriate clinical use of antibiotics can cause an imbalance in the gut flora, resulting in antibiotic-associated diarrhea (AAD). Macrofungal polysaccharides are rich in bioactivities and have attracted much attention for their good performance in anti-inflammatory, antioxidant, anti-obesity and anti-tumor properties. Therefore, we explored the role of Dictyophora indusiata water-insoluble polysaccharides (DIPY) in modulating the gut flora to improve AAD.MethodsWe initially prepared the water-insoluble polysaccharides derived from Dictyophora indusiata. Subsequently, by comprehensively evaluating multiple parameters including the body weight, dietary patterns, cecal histomorphological characteristics, intestinal microbiota composition, concentrations of short-chain fatty acids (SCFAs), and the levels of inflammatory factors in the antibiotic-associated diarrhea (AAD) model animals, we delved into both the action mechanisms of these polysaccharides and their impacts on the intestinal flora and metabolites within C57BL/6J mice.ResultsOur results showed that DIPY effectively ameliorated AAD in mice by modulating the intestinal flora, increasing microbial diversity, the Shannon and Ace index was significantly higher in the DIPY group than in the NR group after the DIPY intervention (p < 0.001). Also, compared with the NR group, DIPY increasing the relative abundance of Parasutterella and Blautia, increasing the production of acetic acid (p < 0.001), and decreasing the levels of LPS, MCP-1, TNF-α, and IL-6 (p < 0.05) which attenuating inflammatory responses.ConclusionThis study demonstrated that DIPY has intestinal prebiotic function, which provides a basis for further development of functional products for the treatment of AAD.